New Bounds for Distance Energy of A Graph - G. Sridhara; Rajesh Kanna; H.L. Parashivamurthy (Journal of the Indonesian Mathematical Society, 2020)
For any connected graph G, the distance energy, E_D(G) is defined as the sum of the absolute eigenvalues of its distance matrix.  Distance energy was introduced by Indulal et al in the year 2008. It has significant importance in QSPR analysis of molecular descriptor to study  their physico-chemical properties. Our interest in this article is to establish new lower and upper bounds for distance energy.